KEMANDIRIAN WANITA SINGLE PARENT DALAM MENDIDIK ANAK (Studi Kasus Di Desa Pakang, Andong, Boyolali) - Sumiyatun, Sumiyatun; Muhibbin, Achmad (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The research aims are: 1. to describe the women independency ofbeing single parent to educate their children at pakang village,Andong, Boyolali; 2. To describe the problem of single parentwomen in educate their children at pakang village, Andong,Boyolali.The indicator of women independency of being singleparent are: 1. Can complete duty, 2. Responsible, 3. Able to overcome theproblem, 4. Believe in their own ability, 5. Able to manage themselves. Thisresearch used two triangulation methods, those are: data gathering techniqueand data gathering source. Data collections used are: participativeobservation, in depth interview, and documentation. Data analysis used isqualitative descriptive with interactive analysis model, including: datagathering, data reduction, data presenting, and drawing conclusion. Theresearch result showed that; 1. The women independency of being singleparent to educate their children at pakang village, Andong, Boyolali, includingphysical, intellectual, and spiritual education. 2. The problem faced by singleparent women to educate their children including internal and externalproblem. The main internal problem is parent and their own children. Externalproblem is their playing and school environment. 3. Problem solution that isused by single parent women for internal; the parent should always giveenough pay attention and independency to their children. For external: theparent should plant Islamic values in their environment and choosing anappropriate school for their children in order to get the best attitude andbehavior.